Philosophy and Ethics: a resource for units 1A-1B - Millett, Stephan; Tapper, Alan (Impact Publishing, 2008)
This book is written specifically for students studying Units 1A and 1B of the Philosophy and Ethics Course, in accordance with Curriculum Council guidelines. It will guide teachers through the difficult process of coming to terms with how best to deliver the new course. It provides full explanations of concepts and debates, and is packed with activities to engage students and maintain their interest, whilst clarifying a variety of concepts. 'Community of Inquiry' activities are also included.